2017
DOI: 10.1039/c7ob01406f
|View full text |Cite
|
Sign up to set email alerts
|

2-Nitroimidazole based fluorescent probes for nitroreductase; monitoring reductive stress in cellulo

Abstract: Two 2-nitroimidazole-1,8-naphthalimide conjugates, 1 and 2, have been synthesised as fluorescence probes for the detection of reductive stress in HeLa cells. The 4-substituted derivative 1 was shown to act as a highly sensitive and selective substrate for nitroreductase where it exhibited a clear blue to green ratiometric fluorescence response visible to the naked eye. Moreover, biological studies demonstrated 1 could be activated in cellulo where the impact of reductive stress was easily monitored using confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…The rationale behind our design is based on the precedent that isonitriles convert tetrazines into 4-aminopyrazoles 35,36 and that 5membered heterocycles with amine substituents spontaneously eliminate diverse functional groups. 40,41 In a series of experiments, we demonstrated that TzMe-modied molecules reacted readily with isonitriles to release amines (from tetrazylmethyloxycarbonyl (Tzmoc) derivatives) and phenols ( Fig. 2a).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind our design is based on the precedent that isonitriles convert tetrazines into 4-aminopyrazoles 35,36 and that 5membered heterocycles with amine substituents spontaneously eliminate diverse functional groups. 40,41 In a series of experiments, we demonstrated that TzMe-modied molecules reacted readily with isonitriles to release amines (from tetrazylmethyloxycarbonyl (Tzmoc) derivatives) and phenols ( Fig. 2a).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent probes are a powerful tool for direct visualization of biomolecules in vivo with high sensitivity and short response times. 21,22 To date, several detection methods for reductive stress have been reported, [23][24][25] and in particular, several small-molecule uorescent probes for detecting NAD(P) H have been developed. [26][27][28][29][30][31] Louie et al synthesized a NADHsensitive multimodal magnetic-resonance/optical-imaging contrast agent and successfully applied it in cells.…”
Section: Introductionmentioning
confidence: 99%
“…From our work on squaramides we are familiar with the self-assembly/aggregation of these molecules due to bidirectional H-bonding interactions in addition to π-π stacking brought about by the aromatic cyclobutenedione ring (Elmes et al, 2013, 2014, 2015; Busschaert et al, 2014; Elmes and Jolliffe, 2014; Qin et al, 2016; Marchetti et al, 2018). Moreover, we have also gained considerable experience working with the naphthalimide fluorophore which has fluorescence properties that are highly dependent upon aggregation (Elmes and Gunnlaugsson, 2010; Elmes et al, 2012; Ryan et al, 2012, 2015; Ao et al, 2017). Indeed, Scanlan, Gunnlaugsson and co-workers have recently shown glycosylated naphthalimide and naphthalimide Tröger's bases that act as fluorescent aggregation probes for the Con A protein where both structures self-assemble in solution to form supramolecular structures by head-to-tail π-π stacking and extended hydrogen bonding interactions (Calatrava-Pérez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%